1992
DOI: 10.1007/bf00319010
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive phenology of desert and Mediterranean populations of annual plants grown with and without water stress

Abstract: The dynamics of vegetative and reproductive growth were compared in matched pairs of Mediteranean and desert populations of three unrelated annual species, Erucaria hispanica (L.) Druce, Brachypodium distachyon (L.) Beauv. and Bromus fasciculatus C. Presl., under high and low levels of water availability in a common-environment experiment. Plants of all desert populations showed earlier switches to reproductive development and to subsequent phenophases, and the transition to flowering occurred at smaller plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
146
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(161 citation statements)
references
References 37 publications
14
146
1
Order By: Relevance
“…Increasing aridity leads to shortening of growing season, and populations from arid habitats were found to flower earlier than in more mesic sites in many annual and perennial species (Aronson et al, 1992;Bennington and McGraw, 1995;Del Pozo et al, 2002;Eckhart et al, 2004;Franke et al, 2006;Hall and Willis, 2006;Volis, 2007). Selection for advance of flowering was found in several studies with experimentally induced drought stress (Stanton et al, 2000;Volis et al, 2004;Franks et al, 2007) and in a reciprocal transplant experiment with one desert and one Mediterranean site (Volis et al, .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing aridity leads to shortening of growing season, and populations from arid habitats were found to flower earlier than in more mesic sites in many annual and perennial species (Aronson et al, 1992;Bennington and McGraw, 1995;Del Pozo et al, 2002;Eckhart et al, 2004;Franke et al, 2006;Hall and Willis, 2006;Volis, 2007). Selection for advance of flowering was found in several studies with experimentally induced drought stress (Stanton et al, 2000;Volis et al, 2004;Franks et al, 2007) and in a reciprocal transplant experiment with one desert and one Mediterranean site (Volis et al, .…”
Section: Discussionmentioning
confidence: 99%
“…Small leaves and early flowering are both characteristic of desert annuals and are thought to be of adaptive significance. In general, small leaves can reduce water loss and prevent heat stress while early flowering enables seed production before the onset of strong summer drought (Givnish 1979;Fox 1989;Aronson et al 1992Aronson et al , 1993Smith et al 1997;Gibson 1998). Both of these traits were negatively transgressive in a previous greenhouse study, implying strong genetic control (Rosenthal et al 2002).…”
Section: Transgression In the Hybrid Speciesmentioning
confidence: 96%
“…Experiments of this nature are carried out either in the field or under common garden or greenhouse conditions, where water availability has been shown to affect integral elements of population dynamics. In particular, additional precipitation increases germination [63,64], biomass [10] and fecundity [64], while precipitation deficit leads to a shortened life cycle, expedited flowering [65] and higher reproductive effort [30]. However, multi-species experiments have shown that these responses are not ubiquitous and, often, coexisting species do not respond at all to changes in water availability [10,30].…”
Section: Precipitation Global Environmental Change and Desert Plantmentioning
confidence: 99%